Immunotherapy for Alzheimer’s disease: past, present and future - Spencer, Brian; Masliah, Eliezer (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) is an incurable, progressive, neurodegenerative disorder affecting over 5 million people in the US alone. This neurological disorder is characterized by widespread neurodegeneration throughout the association cortex and limbic system caused by deposition of Aβ resulting in the formation of plaques and tau resulting in the formation of neurofibrillary tangles. Active immunization for Aß showed promise in animal models of Alzheimer’s disease; however, the models were unable to predict the off-target immune effects in human patients. A few patients in the initial trial suffered cerebral meningoencephalitis. Recently, passive immunization has shown promise in the lab with less chance of off-target immune effects. Several trials have attempted using passive immunization for Aß, but again, positive end points have been elusive. The next generation of immunotherapy for Alzheimer’s disease may involve the marriage of anti-Aß antibodies with technology aimed at improving transport across the blood-brain barrier. Receptor mediated transport of antibodies may increase CNS exposure and improve the therapeutic index in the clinic.